2015
DOI: 10.1038/srep15122
|View full text |Cite
|
Sign up to set email alerts
|

Coculture of Primary Motor Neurons and Schwann Cells as a Model for In Vitro Myelination

Abstract: A culture system that can recapitulate myelination in vitro will not only help us better understand the mechanism of myelination and demyelination, but also find out possible therapeutic interventions for treating demyelinating diseases. Here, we introduce a simple and reproducible myelination culture system using mouse motor neurons (MNs) and Schwann cells (SCs). Dissociated motor neurons are plated on a feeder layer of SCs, which interact with and wrap around the axons of MNs as they differentiate in culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 37 publications
(52 reference statements)
7
66
0
Order By: Relevance
“…The increased MBP level and enhanced thickness of myelination replicated our previous study involving 2D coculture (Hyung et al, 2015). We tested the effects of optogenetic stimulation at DIV 10 and 20, which we had identified in SCs at the premyelinating and myelinating stages, respectively.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The increased MBP level and enhanced thickness of myelination replicated our previous study involving 2D coculture (Hyung et al, 2015). We tested the effects of optogenetic stimulation at DIV 10 and 20, which we had identified in SCs at the premyelinating and myelinating stages, respectively.…”
Section: Discussionsupporting
confidence: 63%
“…), as described previously (Hyung et al, 2015;Suh & Hyung, 2018). MNs were harvested from spinal cords (L1-L6 segments) of E13 mouse embryos and cultured in neurobasal/B27 (GibcoA) medium supplemented with 10% horse serum (Gibco), 1% penicillin/ streptomycin (P/S; Sigma), 0.5 mM L-glutamine (Invitrogen), 1 mM β-mercaptoethanol (Sigma), and 50 µg/ml BDNF (Prospec.…”
Section: Preparation Of Mn and Sc Culturesmentioning
confidence: 99%
“…The relevance of Krox‐20 to SC maturation is unequivocally illustrated in studies on mutations in the EGR2 gene associated with peripheral myelinopathies, including Charcot‐Marie‐Tooth syndrome . Inhibition of Krox‐20 is also observed in non‐hereditary demyelinating neuropathies, such as Guillain‐Barré syndrome . In line, our results demonstrate that ML decreases the frequency of murine SCs expressing Krox‐20 in vivo and in vitro, suggesting that the bacillus may hinder the myelinating phenotype in these cells.…”
Section: Discussionsupporting
confidence: 77%
“…We previously showed that the viability of MNs could be markedly enhanced by culturing neurons on top of a confluent feeder layer of SCs (Hyung et al, ). To examine if the increased viability of MNs required a direct cell–cell contact with SCs or was mediated by soluble factors secreted from SCs, we cultured SCs and MNs in a transwell coculture system in which the two types of cells were seeded in different compartments separated by a porous membrane insert (Figure a): MNs were plated and cultured on a coverslip placed in a culture well (bottom compartment), whereas SCs were seeded on a removable transwell membrane insert (upper compartment).…”
Section: Resultsmentioning
confidence: 99%